Heavy metal concentration in surficial sediments from Anzali wetland - Gh. Amini ranjbar (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1994)
Concentrations of Cd, Pb, Cu, and Zn were determined in surficial sediments from II sampling sites in Anzali wetland. Four different methods were tested to choose the most efficient procedure for determi-nation of the metals including: 1) HNO3-HCL digestion 2) HCL digestion 3) HNO3 digestion 4) Extraction with EDTA. The measurement of the metal levels was performed using atomic absorption spectroscopy. In order to interpret analytical results, several statistical methods were applied. There was statistically significant differences between the accumulation of the metals in sediments. While considerable differences could not be observed between the seasons. Different patterns could be detected at the levels of each heavy metal in the sampling sites. The sampling site eight showed the lowest similarity compared to others......